Quantifying the Effects of Refactorings on Bad Smells - Tavares, Cleiton Silva; Bigonha, Mariza A. S.; Figueiredo, Eduardo (Anais Estendidos do Congresso Brasileiro de Software: Teoria e Prática (CBSoft); 2020: Anais Estendidos do XI Congresso Brasileiro de Software: Teoria e PráticaDO - 10.5753/cbsoft_estendido.2020.14615, 2020)
Refactoring aims to remove bad smells and increase software maintainability by improving the software structure without changing its behavior. Even with the existence of tools to assist refactoring, many developers do not trust in their solutions, claiming that some studies show that refactoring may even introduce new bad smells into the source code. However, we do not find a complete catalog that states when this may occur. To investigate this subject deeply, the goal of this dissertation is to evaluate the effects of refactoring on the detection of bad smells. Specifically, we want to know if and what refactoring removes bad smells or introduces them. To achieve our goal, we plan to conduct empirical studies to provide a catalog showing these situations.